Reflections on the Aftermath of the Arab Spring (American Journal of Islam and Society, 2015)
On November 18, 2014, Datuk Seri Anwar Ibrahim, founder and board member,IIIT; leader of the Malaysian opposition; and former deputy prime ministerof Malaysia, shared his “Reflections on the Aftermath of the Arab Spring” withthe general public at the IIIT headquarters in Herndon, VA.He opened with “O you who believe! Obey Allah and obey the Apostleand those in authority from among you” (Q. 4:59), which he considers one ofthe Qur’an’s “most used and abused verses.” In addition to being used to supportdemocracy, it is abused by many others to demand the masses’ supportfor dictators, authoritarian, and military junta rule regardless of how they aretreated. This verse also highlights an issue that has rocked the Arab world eversince December 17, 2010, when Tunisian street vendor Mohamed Bouazizi sethimself on fire to protest the continued abuse and harassment inflicted uponhim by the Tunisian police force: the issue of governmental legitimacy, whichis a problem in both the West and the Muslim world. Anwar stated that thegovernment must represent a majority consensus, respect some process (e.g.,democracy), and allow people the freedom of expression so that they can expresstheir support, disgust, or opposition.The Arabs’ demand for legitimate governance has been on the mind ofIIIT as well, for its leaders have spent the last decade addressing this concernfrom the point of view of the maqāṣid. Anwar traced this concern back to along-ago meeting when several of the IIIT founders were discussing why therewas no Muslim equivalent of the “Western canon,” the “Great Books,” a “greatintellectual tradition.” This was the start of an ongoing process to fill this gapin contemporary Muslim literature.The outbreak of Arab Spring clearly revealed that there is still a need todeal with ethics in governance, for lasting reform can only be actualized inthe form of systems. The ongoing abuse, corruption, repression, and brutalityinflicted upon the people by their own leaders is, according to him, something ...